Penegakan Hukum Lingkungan Hidup di ASEAN: Perbandingan antara Negara Anggota dan Implikasinya thd Keberlanjutan Lingkungan - Runtunuwu, Yoan Barbara (Jurnal Mahkamah Hukum, 2025)
This study aims to analyze environmental law enforcement mechanisms in ASEAN member countries and examine their implications for regional environmental sustainability. Using a normative legal approach combined with comparative case studies, this study analyzes secondary data in the form of laws and regulations, international agreements, scientific journals, and official reports from Indonesia, Malaysia, Singapore, Thailand, and Vietnam. The analysis is conducted qualitatively using comparative techniques to identify differences in legislative frameworks, institutional capacity, oversight mechanisms, and enforcement effectiveness. The results show significant variations in the effectiveness of environmental law enforcement, with Singapore having the most effective system (Environmental Performance Index ranking 39) and Vietnam (ranking 141). This disparity impacts regional environmental sustainability, as evidenced by transboundary environmental problems such as haze, which causes economic losses of USD 16.1 billion per year. Countries with effective law enforcement exhibit better air quality (Singapore's PM2.5 12 μg/m³ vs. Vietnam's 35 μg/m³) and higher levels of industrial compliance (Singapore's 94% vs. Vietnam's 48%). This study recommends strengthening national capacity, regional harmonization, and increasing ASEAN cooperation to achieve optimal environmental sustainability.